Clinicopathological Features and Prognoses in Patients With Brain Metastases From Small-Cell Esophageal Carcinoma: A Retrospective Analysis of 18 Patients - Wenpeng Jiao; Chi Lin; Linlin Xiao; Xinyuan Zhang; Mengzhu Hu; Min Zhao; Jun Wang (Frontiers in Oncology, 2021)
Objective: This study aims to examine the clinical characteristics of patients with brain metastases (BM) from small-cell esophageal carcinoma (SCEC) and to explore the association of the corresponding factors with overall survival (OS).Methods: The data of 18 patients with brain metastases from SCEC, diagnosed from January 1, 2006, to December 31, 2018, in the Fourth Hospital of Hebei Medical University were analyzed retrospectively.Results: The 18 patients who were included in this study accounted for 6.7% of the patients with SCEC diagnosed from 2006 to 2018. Of the 18 patients, 8 (44.4%) were females. For the entire cohort, the median OS was 7 months, the 1-year OS was 22.2%, and the 2-year OS was 0%. For patients who received whole-brain radiotherapy (WBRT) and for those who did not (13 vs. 5), the median OS was 11.9 and 3 months, respectively, and the 1-year OS was 30.8 and 0%, respectively. When comparing diagnosis-specific Graded Prognostic Assessment (DS-GPA) scores of patients with BM from SCEC ranging from 2.5 to 4 and from 0 to 2, the median OS was 13.1 and 4 months, respectively, and the 1-year OS was 57.1 and 0%, respectively. In the univariable regression, patients who received WBRT had improved OS compared to those who did not (HR = 0.249, p = 0.018), and patients with a DS-GPA score of 2.5–4 were associated with improved OS compared with patients with a DS-GPA score of 0–2 (HR = 0.050, p = 0.005).Conclusion: The incidence of brain metastases in patients with SCEC is low, but the prognosis in those patients is very poor. The DS-GPA score may be a prognostic factor of patients with BM from SCEC. Brain radiotherapy could improve the survival of these patients.